Encyclopaedic dictionary of geography - Adams, Andrew S. (Pentagon Press New Delhi, India, 2004)
The Encyclopaedic Dictionary of Geography is a comprehensive reference book that provides detailed definitions, explanations, and insights into key geographical terms, concepts, and phenomena.